Synthesis of hickory biochar via one-step acidic ball milling: Characteristics and titan yellow adsorption - Yang, Xiaodong; Wang, LiLi; Tong, Jin; Shao, Xueqin; Chen, Rui; Yang, Qiang; Li, Fangfei; Xue, Bing; Li, Guodong; Han, Ye; Yang, Xizhen; Zimmerman, Andrew R.; et al. (Journal of cleaner production, 2022)
Biochar has attracted considerable attentions for its potential in many environmental and industrial applications. Here, a novel facile and efficient one-step acidic ball milling approach was designed to fabricate a porous biochar directly from hickory wood without any external heat treatment. After characterization, the biochar was tested for its ability to remove Titan Yellow (TY) organic dye from aqueous solution. Compared to the pristine ball milled biomass (BMB), the acidic ball milled biochar (ABMB) had a greater degree of carbonization and a larger diversity of oxygen-containing functional groups. As a result, the ABMB sorbed 23 times more TY dye than BMB (maximum sorption capacities of 182.3 and 8.1 mg g−1, respectively). Freundlich isotherm and intraparticle diffusion kinetic models best described the TY adsorption by ABMB and BMB. The results suggest that the one-step acidic ball milling method has great potential as a convenient and efficient approach to convert biomass to biochar with excellent characteristics for environmental remediation and perhaps water treatment applications. [Display omitted] •Biochar (ABMB) was fabricated by one-step acidic ball milling without heat treatment.•Acid treatment improved biochar's surface functional groups and functionality.•One-step acidic ball milling is promising to converting biomass to biochar.•As-prepared ABMB sorbed 182.3 mg/g of titan yellow (TY).•Adsorption of TY onto ABMB was more than 80% after 5 regeneration cycles.